Influence of the Surfactant Structure on Photoluminescent π-Conjugated Polymer Nanoparticles Interfacial Properties and Protein Binding - Urbano, Laura (Langmuir : the ACS journal of surfaces and colloids, 2018)
π-Conjugated polymer nanoparticles (CPNs) are under investigation as photoluminescent agents for diagnostics and bioimaging. To determine whether the choice of surfactant can improve CPN properties and prevent protein adsorption, five nonionic polyethylene glycol alkyl ether surfactants were used to produce CPNs from three representative π-conjugated polymers. The surfactant structure did not influence size or yield, which was dependent on the nature of the conjugated polymer. Hydrophobic interaction chromatography, contact angle, quartz crystal microbalance, and neutron reflectivity studies were used to assess the affinity of the surfactant to the conjugated polymer surface and indicated that all surfactants were displaced by the addition of a model serum protein. In summary, CPN preparation methods which rely on surface coating of a conjugated polymer core with amphiphilic surfactants may produce systems with good yields and colloidal stability in vitro, but may be susceptible to significant surface alterations in physiological fluids